Local and landscape drivers of aquatic‐to‐terrestrial subsidies in riparian ecosystems: a worldwide meta‐analysis. Issue 4 (9th April 2019) - Lafage, D.; Bergman, E.; Eckstein, R. L.; Österling, E. M.; Sadler, J. P.; Piccolo, J. J.
Abstract: Cross‐boundary fluxes of organisms and matter, termed "subsidies, " are now recognized to be reciprocal and of roughly equal importance for both aquatic and terrestrial systems, even if terrestrial input to aquatic ecosystems has received most attention. The magnitude of aquatic‐to‐terrestrial subsidies is well documented, but the drivers behind these subsidies and their utilization by terrestrial consumers are characteristically local‐scale studies, limiting the inferences that can be drawn for broader geographic scales. We therefore built and analyzed a database of stable isotope data extracted from 21 studies worldwide, to identify both landscape‐scale (catchment) and local‐scale (100‐m riparian zone) variables that may affect the diet of terrestrial predators in riparian ecosystems. Our meta‐analysis revealed a greater magnitude of aquatic‐to‐terrestrial subsidies (>50%) than previously reported, albeit with large geographic and inter‐annual variations. Moreover, we demonstrated a large effect of landscape‐scale factors on aquatic‐to‐terrestrial subsidies, particularly anthropogenic land use and tree cover. Local human population was the only relevant factor at the local scale. We also found that studies on landscape‐scale and anthropogenic land use effects on aquatic‐to‐terrestrial subsidies are strongly under‐represented in the ecological literature, which limits the general inferences that can currently be drawn about landscape effects. We suggest that landscape‐scale studies could improve our understanding of how land use and environmental change might influence future patterns of biodiversity and ecosystem function.